Effects of leaf removal and cluster thinning on yield and quality of grapes (vitis vinifera l., riesling × silvaner) in corrales, boyaca (colombia) (2011)
The vineyards that are located in the Colombian cool tropicalzone of Corrales (Boyaca department) offer grapes for the production of quality wines; to improve the crop we must know the adequate balance between the quantity of clusters and the leaf area of the plants. In order to determine the effect of leaf removal and cluster thinning on yield and quality of the clonal selection Riesling × Silvaner wine grape, it was used a completely randomized bifactorial design of 2x3. The first factor was removal of leaves (without defoliation and 60% defoliation) and the second one was cluster thinning (maintaining 66% or 33% of clusters per plant). Plants with 66% clusters and without leaf removal exhibited the highest total soluble solids content and yield of grapes, in fresh mass of clusters and fresh and dry mass of grapes. Plants without cluster thinning, but with removal of leaves, produced the lowest pH levels and total titratable acidity in the grapes. The technical maturity index was significantly higher in plants without leaf thinning; but was not affected by removed clusters. Thinning clusters is an alternative to improve production and the quality of wine grapes.